PWR: work&labour news&research - Centre for Industrial Relations and Human Resources Library (University of Toronto) (2012)
The latest information in Industrial Relations and Human Resources, from the CIRHR Library at the University of Toronto. Stories from the tumblr are collected weekly in PWR: work&labour news&research, which is published from September to June. –Publisher's description.
https://cirhr.library.utoronto.ca/